Top Management Team Structure and Firm Financial Performance : Evidence from Listed US Companies - KC, Ritu Sobha; Kshetri, Bedana (My University, 2026)
This thesis examines the impact of the structure of the top management team (TMT) on the financial performance of U.S. firms. This study analyses the extent to which there is a significant influence on the business profitability by important structural attributes of TMTs (team size, gender diversity and CEO duality) through the Upper Echelons Theory. Here, Return on Equity (ROE) and Return on Assets (ROA) are used to measure firms financial performance. The study applies panel regression analysis with year and industry fixed effects using data from 2011 to 2020. The result show that the gender diversity in the TMT is positively associated with financial performance while the TMT size shows negative relationship with firm’s profitability. Whereas the dualism of CEOs does not always have a statistically significant association and consistent impact on business financial performance. There appears to be little effect of firm age, but firm size and leverage have a range of effects between the control factors. Altogether, the findings indicate that not every aspect of TMT structure equally influences the firm outcomes, which to some degree confirms the Upper Echelons Theory. The study contributes to the literature on corporate governance by delivering empirical evidence on top management structure along with promoting gender diversity at the top management level of the U.S. companies. These results can also be useful to the corporate leaders and legislators who are developing effective governance systems to enhance the performance of businesses.
Keywords: business leaders; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance